2019
DOI: 10.1038/s41467-019-10707-x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell clonal expansion in the development of cerebral cavernous malformations

Abstract: Cerebral cavernous malformation (CCM) is a neurovascular familial or sporadic disease that is characterised by capillary-venous cavernomas, and is due to loss-of-function mutations to any one of three CCM genes. Familial CCM follows a two-hit mechanism similar to that of tumour suppressor genes, while in sporadic cavernomas only a small fraction of endothelial cells shows mutated CCM genes. We reported that in mouse models and in human patients, endothelial cells l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 52 publications
7
128
1
Order By: Relevance
“…Our data also illustrate that the lining endothelium within human cavernous tissues is not a homogeneous cellular compartment of ECs that all had acquired a second postzygotic loss-of-function variant ( CCM1 −/− ), but a mosaic of ECs with retained CCM1 expression and with complete CCM1 inactivation. This observation is reminiscent to what has recently been shown in two mouse models for CCM3, in which endothelial mosaicism of mutant and wild-type ECs was observed in expanded lesions 13 14. Similarly, the large cavernoma of our index patient is most likely the product of a clonally expanded CCM1 −/− EC and heterozygous CCM1 +/− ECs (figure 1G).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data also illustrate that the lining endothelium within human cavernous tissues is not a homogeneous cellular compartment of ECs that all had acquired a second postzygotic loss-of-function variant ( CCM1 −/− ), but a mosaic of ECs with retained CCM1 expression and with complete CCM1 inactivation. This observation is reminiscent to what has recently been shown in two mouse models for CCM3, in which endothelial mosaicism of mutant and wild-type ECs was observed in expanded lesions 13 14. Similarly, the large cavernoma of our index patient is most likely the product of a clonally expanded CCM1 −/− EC and heterozygous CCM1 +/− ECs (figure 1G).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, only little experimental evidence has been published to support a genetic two-step inactivation of CCM1, CCM2 and CCM3 (table 1). 8–12 Recent data from two murine models implicate that clonal expansion of ECs after biallelic Ccm3 inactivation initiates cavernoma formation, while incorporation of ECs without a second mutation contributes to their growth 13 14. Lately, a novel human EC culture model specified that CCM3 inactivation results in a survival benefit of functionally impaired ECs that are unable to form spheroids 15…”
Section: Introductionmentioning
confidence: 99%
“…Considering that our group recently reported that cavernomas have clonal origins from expansion of Pdcd10 -ko progenitor cells ( Malinverno et al, 2019 ), we investigated the distribution of cells that expressed progenitor cell markers in the STREAM-generated trajectories. We therefore quantified each branch for the proportions of cells positive for Bst1 , Peg3 , Procr , and Cd200 (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Normal intussusceptive angiogenesis requires an orderly patterning of high and low flow signaling 33 The dilated multi-cavernous CVP lesions described here resemble human multicavernous CCM 3 and their formation required mosaicism. Recent elegant studies found that multi-cavernous murine CCM are mosaic for inactivation of Ccm3 45,46 . The mouse studies emphasized that simply dilated vessels are not mosaic and contained only Ccm3 null endothelial cells 45,46 .…”
Section: Ccm2 Mosaicism Causes Multi-cavernous Malformationsmentioning
confidence: 99%